2021
DOI: 10.3389/fpsyt.2021.694575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness-Based Cognitive Therapy on Stigma in Female Patients With Schizophrenia

Abstract: Mindfulness-based cognitive therapy (MBCT) has been increasingly recognized as effective in different mental illnesses, but these effects are limited in schizophrenia. For patients with schizophrenia, stigma is one of the most negative factors that affects treatment, rehabilitation and social function. This research aimed to determine the effects of MBCT on stigma in patients with schizophrenia. In total, 62 inpatients with schizophrenia were recruited and randomly assigned to the experimental group or control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The findings of the intervention effect of developing mindfulness skills among the examined patients, as measured by the FFMQ, backed up the effect of MBI on reducing positive and negative symptoms and enhancing recovery. After the seven sessions, the patients in the intervention group had a substantial increase in self-reported mindfulness, showing that the intervention increased participants' awareness of mindfulness, which was consistent with prior MBI studies (Tabak et al, 2015& Tang et al, 2021. Fortunately, the results of the current study are closely interrelated, and this has been shown in the positive impact of the program on the three variables measured by the study, as the results of the study proved that total positive and negative symptoms score correlated significantly and negatively to five total facet mindfulness score and total recovery assessment score.…”
Section: Discussionsupporting
confidence: 85%
“…The findings of the intervention effect of developing mindfulness skills among the examined patients, as measured by the FFMQ, backed up the effect of MBI on reducing positive and negative symptoms and enhancing recovery. After the seven sessions, the patients in the intervention group had a substantial increase in self-reported mindfulness, showing that the intervention increased participants' awareness of mindfulness, which was consistent with prior MBI studies (Tabak et al, 2015& Tang et al, 2021. Fortunately, the results of the current study are closely interrelated, and this has been shown in the positive impact of the program on the three variables measured by the study, as the results of the study proved that total positive and negative symptoms score correlated significantly and negatively to five total facet mindfulness score and total recovery assessment score.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the theoretical support for a potentially protective role of mindfulness against stigma towards patients with mental illness, the lack of research conducted in this regard is noteworthy. Some studies have demonstrated beneficial effects of mindfulness for self-stigma among patients with mental illness (Martin et al, 2020 ; Tang et al, 2021 ), but the effects on public stigma and stigma among healthcare professionals remain unexplored. In this setting, we set out to investigate whether trait mindfulness and facets of mindfulness were associated with lower stigma among nurses towards psychiatric patients, and to investigate whether compassion towards others acts as a mediator in these relationships.…”
mentioning
confidence: 99%
“…[ 40 ], Gumley et al. [ 35 ], and Yang and Zhu [ 41 ]. Nineteen studies arranged for home practice, either compulsory or non-compulsory, following guided sound-tracks or the completion of a log book.…”
Section: Resultsmentioning
confidence: 99%